How Successful Are U.S. Adults at Altering Nutrient Intakes and Meeting Dietary Guideline Recommendations?. (29th May 2020) - Kluger, Alexandria; Lieberman, Harris; Pasiakos, Stefan; Fulgoni, Victor; Berryman, Claire
Abstract: Objectives: The Dietary Guidelines for Americans (DGAs) recommend dietary patterns that limit added sugar, sodium, and saturated fat and emphasize nutrient-dense foods. It is unknown whether individuals who self-report adhering to a diet that alters nutrient intake are, in fact, meeting DGA recommendations. Objective: To compare dietary intakes and adherence to the DGAs in individuals who self-report following a special diet versus those who report following no diet. Methods: NHANES 2003–2014 (≥19 y, n  = 30, 086) data were analyzed to determine % of the population answering yes or no to "Are you on any type of special diet?". Individuals who answered yes, were further asked, "What kind of diet are you on?" and chose from a list of special diets (e.g., low salt or sodium; sugar free or low sugar). Mean nutrient intakes for each diet population were compared to the population following no diet. Individual usual intakes were estimated to determine the % of the population above or below nutrient-specific DGA recommendations. P < 0.01 was considered significant. Results: In U.S. adults, 15.6 ± 0.3% answered yes when asked if they adhere to a special diet. Individuals who reported following a low sugar diet ( n  = 208) consumed 8.8 ± 0.7% total daily energy from added sugars, which was less than those following no diet (13.8 ± 0.1%; P < 0.01). Of individuals following a low sugar diet, 67 ± 4% met the recommendation to consume <10% energy from added sugar, which was a greater percentage than those following no diet (32 ± 1%; P < 0.01). Individuals who reported following a low salt/sodium diet ( n  = 580) consumed 3317 ± 110 mg/d sodium, which was less than those following no diet (3657 ± 17 mg/d; P < 0.01). Only 17 ± 2% of individuals following a low salt/sodium diet met recommendations to consume <2300 mg/d sodium, which was a greater percentage than those following no diet (10 ± 0%; P < 0.01). Conclusions: American adults who self-report adhering to a low sugar or low salt/sodium diet consume less added sugar and sodium, respectively, than individuals who report following no diet. However, a substantial proportion of individuals following low sugar or low salt/sodium diets are still not meeting DGA recommendations. Funding Sources: DMRP/USAMRDC. Views expressed are those of the authors and do not reflect official policy of the Army, DoD, or US Government.